Positive error climate promotes learning outcomes through students' adaptive reactions towards errors. (August 2022) - Soncini, Annalisa; Visintin, Emilio Paolo; Matteucci, Maria Cristina; Tomasetto, Carlo; Butera, Fabrizio
Abstract: Errors are an integral part of the learning process and an opportunity to increase skills and knowledge, but they are often discouraged, sanctioned and derided in the classroom. This study tests whether students' perceptions of being part of an error-friendly classroom context (i.e., a positive classroom error climate) is positively related to students' learning outcomes via students' adaptive reactions towards errors. A total of 563 Italian middle school students from 32 mathematics classes completed a questionnaire on their perceptions of classroom error climate and their reactions towards errors. Students' math grades were used as indicators of their level of learning outcomes. A multilevel model showed that perceived classroom error climate was positively related to math grades via increased adaptive reactions towards errors. Our findings revealed that an error-friendly classroom context is associated with students' adaptive adjustment to errors and to better learning outcomes in mathematics. Highlights: Perceiving a positive error climate is associated with students' adaptive reactions towards errors. Students' adaptive reactions towards errors are related to better learning outcomes. Positive error climate is indirectly related to students' learning outcomes.